The most common digital applications implemented in language learning - Fuentes Aguiluz, Alejandra María; Pineda Avalos, Celia Carmina (2024)
This paper compiles some of the best ways to manage a virtual environment, methods, activities, and applications that can be implemented based on the needs of the students and the course, as well as showing the importance of including technologies within the tools to teach content, mainly showing its benefits, this being part of the daily life of both students and teachers. The most common applications and websites used in teaching that can easily be acquired by students as well as showing the way in which a completely virtual and interactive case can be prepared that meets what is necessary to maintain interest of students in the course as if it were developed in the traditional way. The specialization course was divided into 3 modules of 2 months each, in which participants were focus on describing, knowing, and creating their own materials using the applications and websites explained during the course as well as showing their own way on how they can be applied in Language Learning and Language teaching and the development of a virtual environment in a course. KEY WORDS: Synchronous and Asynchronous activities ; E-Learning ; LMS ; Educational tolos ; podcast ; Google site ; Google slides.